Analisis Metode 360 Derajat sebagai Penilaian Kinerja Karyawan Berdasarkan Kompetensi pada Bank Bukopin Kantor Cabang Syariah Medan - Sari, Dian (CV. Kalimasada Group, 2023)
The 360 ​​Degree Method is an assessment that involves many parties such as superiors, subordinates, colleagues, or even yourself. The purpose of this method is used at Bank Bukopin Medan Syariah Branch Office, namely to find out employee performance appraisals, find out the problems faced by employees in the process of implementing employee performance appraisals using the 360 ​​Degree method and to find out what efforts are being made in overcoming performance appraisal problems using 360 Degree Method at Bank Bukopin Sharia Medan Branch Office. This type of research uses descriptive research with a qualitative approach. Data collection was carried out by means of interviews and documentation with several Bank employee representatives. The data used are primary and secondary data from the results obtained directly in the field. The results of this study indicate that the 360 ​​Degree Method plays an important role in assessing employee performance at Bank Bukopin's Medan Sharia Branch Office because it shows objective results because it involves many parties. The assessment is carried out transparently by not mentioning the name of the appraiser and the final results are both discussed at the meeting, attended by all employees with the intention that they know how their performance is and what needs to be developed, must be responsible for their respective obligations in accordance with their fields so that even better in the future.